2009
DOI: 10.3354/ame01303
|View full text |Cite
|
Sign up to set email alerts
|

Comparing electron transport with gas exchange: parameterising exchange rates between alternative photosynthetic currencies for eukaryotic phytoplankton

Abstract: Estimates of aquatic primary productivity derived from in situ active chl a fluorescence have rapidly gained popularity over the past 2 decades. This trend has been driven primarily by the need to improve upon 'conventional' carbon (C) uptake-or oxygen (O 2 ) evolution-based productivity estimates that require water samples to be incubated ex situ. Unlike the conventional approaches to measuring productivity, chlorophyll fluorescence measurements inherently describe only the activity of photosystem II (PSII) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
198
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(207 citation statements)
references
References 71 publications
6
198
1
Order By: Relevance
“…This effect may be compounded in the algae due to their taxonomic and resultant physiological diversity (Suggett, 2011). Suggett et al, (2009) used an FRR fluorometer to measure ETR PSII and examined the relationship between ETR PSII and photosynthesis measured by either gross O 2 production or 14 CO 2 fixation. Measurements were made using six species of eukaryotic phytoplankton, representing a diversity of taxonomic groups.…”
Section: Chlorophyll Fluorescencementioning
confidence: 99%
“…This effect may be compounded in the algae due to their taxonomic and resultant physiological diversity (Suggett, 2011). Suggett et al, (2009) used an FRR fluorometer to measure ETR PSII and examined the relationship between ETR PSII and photosynthesis measured by either gross O 2 production or 14 CO 2 fixation. Measurements were made using six species of eukaryotic phytoplankton, representing a diversity of taxonomic groups.…”
Section: Chlorophyll Fluorescencementioning
confidence: 99%
“…even so, we know that фe:C varies as a function of taxa (Suggett et al 2009b) as well as with different oceanographic provinces and environmental conditions (Lawrenz et al 2013). Indeed, further measures of фe:C are clearly warranted to verify the impacts of the dominant cells' size on this ratio and how this potentially varies across the highly dynamic nutrient-phytoplankton conditions.…”
Section: The Photo-physiological Model: Effects Of Phytoplankton Cellmentioning
confidence: 99%
“…The latter is an approximate ratio found for natural communities dominated by cyanobacteria and small flagellates (Suggett et al 2009b), which was chosen due to the dominance of small cells found in our study, based on the fractionated chlorophyll-a concentration.…”
Section: Etrpsii Primary Production Model Parameterized By the Dominamentioning
confidence: 99%
See 2 more Smart Citations